PENERAPAN METODE DEMONSTRASI DENGAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN BAHASA ARAB - NUR CHAYATIN (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2023)
The research that has been carried out by this researcher is in the form of Classroom Action Research which focuses on students at MTsN 5 Jombang, namely the application of the demonstration method with media images to improve student learning outcomes in Arabic lessons. This research was conducted in 3 cycles, each cycle consisting of the stages of Planning, Action, Observation, Reflection. While the learning approach in this study used the demonstration method through media images that the researchers made in a structured way so that students could build their own knowledge using media images effectively in groups. For data collection through tests, observations, and interviews. The data in this study were obtained from test scores, observations and questionnaires. From the results of the research, an overview was obtained, students obtained ? 67.55 in cycle I of 16 students (40%), cycle II of 27 students (67.5%) and cycle III of 34 students (85%). From the observation results obtained an illustration of an increase in student learning outcomes in learning, namely in the first cycle of 17 students (42.5%), the second cycle of 26 students (65%) and the third cycle of 34 students (85%). As for the results of the questionnaire regarding student responses to learning, it was obtained an overview in cycle I I of 19 students (47.5%), cycle II of 27 students (72.5%) and cycle III of 35 students (87.5%). In learning Arabic with the demonstration method it can improve student learning outcomes as evidenced from cycle I to. cycle III the results always increase in other words children who experience learning difficulties are reduced, while from the observations obtained increased activity, students are actively involved in the learning process. As for the results from the questionnaire, it was found that learning with demonstration methods through media images increased student responses in learning. Thus, research on the application of demonstration methods with media images in Arabic subjects is considered successful. ABSTRAKPada penelitian yang telah dilaksanakan oleh peneliti ini adalah berupa Penelitian Tindakan Kelas yang berfokus pada siswa di MTsN 5 Jombang yaitu penerapan metode demostrasi dengan media gambar untuk meningkatkan hasil belajar siswa pada pelajaran bahasa Arab. Penelitian ini dilaksanakan dalam 3 siklus, masing-masing siklus terdiri atas tahap Perencanaan, Tindakan, Pengamatan, Refleksi. Sedangkan pendekatan pembelajaran dalam penelitian ini menggunakan metode demonstrasi melalui media gambar yang peneliti buat secara berstruktur sehingga siswa bisa membangun pengetahuannya sendiri dengan menggunakan media gambar dengan efektif secara berkelompok. Untuk pengumpulan data melalui tes, observasi, dan wawancara. Adapun data dalam penelitian ini diperoleh dengan nilai tes, observasi dan angket, Dari hasil peneleitian diperoleh gambaran, siswa memperoleh ? 67,55 pada silus I sebesar 16 siswa (40 %), siklus II sebesar 27 siswa (67,5 %) dan siklus III sebesar 34 siswa (85 %). Dari hasil observasi diperoleh gambaran adanya peningkatan hasil belajar siswa dalam pembelajaran yaitu pada siklus I sebesar 17 siswa (42,5 %), siklus II sebesar 26 siswa (65 %) dan siklus III sebesar 34 siswa (85 %). Adapun hasil dari angket tentang respons siswa terhadap pembelajaran diperoleh gambaran pada siklus I I sebesar 19 siswa (47,5 %), siklus II sebesar 27 siswa (72,5 %) dan siklus III sebesar 35 siswa (87,5 %). Dalam pembelajaran bahasa Arab dengan metode demonstrasi dapat meningkatkan hasil belajar siswa terbukti dari siklus I s.d. siklus III hasilnya selalu meningkat dengan kata lain anak yang mengalami kesulitan belajar berkurang, sedangkan dari hasil observasi yang diperoleh peningkatan aktivitas, siswa terlibat aktif dalam proses pembelajaran. Adapun dari angket diperoleh hasil bahwa pembelajaran dengan metode demonstrasi melalui media gambar meningkatkan respons siswa dalam pembelajaran. Dengan demikian bahwa penelitian mengenai penerapan metode demonstrasi dengan media gambar pada mata pelajaran bahasa Arab dianggap berhasil.